Atmospheric Emissions in Nigeria in the Aftermath of COVID-19: A Carbon Foot Print Perspective - Y, Ochu A.; T, Nasidi; Abdulkareem, Jamilu Hassan; H, Abubakar A.; H, Ochu O. (Darul Yasin Al Sys, 2024)
Carbon foot print inclusive, life style changes forced by the covid-19 pandemic has both immediate and long-time effect on diverse facet of human endeavors. Towards quantifying this, secondary emission data was relied upon for time series analysis that showing an increasing trend in emission, further, primary data was obtained via survey procedures for correlation analysis, the result indicates that emissions increase do not necessarily imply to an increase in carbon foot print, as most variables understudied returned a p-value showing disagreement with this assertions, for example, working from home has a significant correlation with spending on transportation with an effect size of .288*and a p value of .022, so also is earnings/income at .260*and a p-value of .039, product reuse and recycle at .484** and a p-value of <.001, Willingness to use alternative energy has increased by an effect size of 266 at p .035 level of significance, indicative of a positive decrease in carbon footprint, in contrast the use of charcoal/fuelwood which has increased post covid-19 with an effect size of 470** p <0.001, patronage of processed product has also increased with an effect size of 325 p .009, as Energy savings and management reduced in post covid-19 period at an effect size of 097 and a p .450 level of significance, with reduced patronage of organic products at an effect size of .096 and a p value of .452 significance. Suggesting that advocacy and public enlightenments is needed to reduce carbon footprint through lifestyle changes related to these aspects. In conclusion the carbon foot print in Nigeria post covid-19 is not Business as usual, total emissions by volume might have increased but some life style changes have significantly reduced individuals carbon footprint. Without which the emissions would have compounded.